2019
DOI: 10.1038/s41598-019-45088-0
|View full text |Cite
|
Sign up to set email alerts
|

Interference effects in quantum-optical coherence tomography using spectrally engineered photon pairs

Abstract: Optical-coherence tomography (OCT) is a technique that employs light in order to measure the internal structure of semitransparent, e.g. biological, samples. It is based on the interference pattern of low-coherence light. Quantum-OCT (QOCT), instead, employs the correlation properties of entangled photon pairs, for example, generated by the process of spontaneous parametric downconversion (SPDC). The usual QOCT scheme uses photon pairs characterised by a joint-spectral amplitude with strict spectral anti-corre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…The signal and idler single-photon wavepackets propagating through the two fiber spools are temporally stretched since different frequencies travel at different group velocities. With adequate calibration, we are able to convert for each coincidence event the time of detection difference across the two output modes from the beam splitter into a measurement of the frequency detuning variable Ω [19,30]. Collecting data from multiple events, we build a histogram which corresponds to an experimental measurement of the joint spectral intensity for the signal and idler photons emerging from the HOM beamsplitter output ports.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal and idler single-photon wavepackets propagating through the two fiber spools are temporally stretched since different frequencies travel at different group velocities. With adequate calibration, we are able to convert for each coincidence event the time of detection difference across the two output modes from the beam splitter into a measurement of the frequency detuning variable Ω [19,30]. Collecting data from multiple events, we build a histogram which corresponds to an experimental measurement of the joint spectral intensity for the signal and idler photons emerging from the HOM beamsplitter output ports.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed a fiber-based QOCT system that incorporates spectrally engineered photon pairs in the telecom regime. We demonstrated interesting interference effects which depend on the type of frequency entanglement [19]. In terms of axial resolution, beyond the quantum-conferred improvement factor of 2, it is possible to incorporate spectral engineering in the form of chirped, aperiodically poled nonlinear crystals to obtain submicrometer resolutions [20,21]; alternatively, a Fisher information analysis can result in attosecond resolutions [22].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this reduction is the most effective when the spectral fragments allow for at least five oscillations of an artefact. Interestingly, this algorithm can be treated as a numerical equivalent of an experimental artefact suppression used by Graciano et al 31 in Td-Q-OCT. In their system, they used a broadband pump laser to generate a joint spectrum which is broad in the anti-diagonal direction.…”
Section: δKmentioning
confidence: 99%
“…Entanglement of photon-pairs has found to have a key role in various imaging experiments beating classical limits [335][336][337][338][339]. Entangled photon-pairs are also used for practical realization of various quantum-enhanced sensing and imaging technologies such as quantum lithography [340][341][342][343], quantum ellipsometry [344,345], quantum optical coherence tomography [346][347][348][349], clock synchronization [350] and optical gyroscope [351].…”
Section: Quantum Communicationmentioning
confidence: 99%